Incidence of Developmental Venous Anomalies in Patients With Multiple Sclerosis: A 3 Tesla MRI Study - Magyar, Marton; Gattringer, Thomas; Enzinger, Christian; Hassler, Eva; Partl, Richard; Khalil, Michael; Reishofer, Gernot; Deutschmann, Hannes; Fazekas, Franz (Frontiers in Neurology, 2022)
Objectives: There is evidence of involvement of the venous system in multiple sclerosis (MS). If this bears also an association with the frequency and extent of developmental venous anomalies (DVAs) is yet unclear. We therefore attempted to investigate this in patients with different phenotypes of MS and in comparison to a control population. Methods: We analyzed the contrast-enhanced T1-weighted MR scans of 431 patients (clinically isolated syndrome - CIS, n=108; MS, n=323) and of 162 control individuals for the presence of a DVA. We also measured the size of the DVA and draining vein and compared the DVA frequency between MS phenotypes. Results: A DVA was found in 38 (8.8 %) of patients with CIS or MS and in 11 (6.8%) controls (p=0.4). DVA frequency was highest in CIS (14.8%) and lowest in progressive MS (4.0%). The mean craniocaudal and axial extension of the DVAs was significantly lower in MS patients than controls (p < 0.05). Conclusions: The frequency of DVAs in MS patients is similar to that in controls. Whether DVA size and appearance may change over time will have to be investigated in a longitudinal manner and with larger sample size.